An Assessment of Practical Skill Learning Activities in Study Materials Developed by the National Open University of Nigeria - Iwuchukwu, Onyeka; Ofoha , Dorothy (West African Journal of Open and Flexible Learning, 2026)
Tertiary institutions across the globe are created with the goal to equip learners with both theoretical and practical knowledge to enable them function in their day-to-day lives. Programmes that are built on skills and knowledge are equally the main focus in the National Open University of Nigeria (NOUN). Research suggests that Nigerian educational system tends to prepare students only with theoretical knowledge. How this reflects in open and distance learning (ODL) is not yet known. Since study materials are the vital tools used in instructional delivery, this study assessed the level of practical skill learning elements embedded in the design and development of course materials used by NOUN students. This was with a view to determining whether or not they were tailored to equip learners with practical skills. The descriptive survey design was adopted for the study. From the University’s archives, 43 copies of printed course materials were randomly selected from variety of courses under various programmes from the five schools to form the sample for the study. The selected course materials were critically examined by 43 subject experts to obtain data on the following: (i)total number of learning objectives in each course module (ii) number of objectives that were stated in measurable behavioural terms presumed to test knowledge (iii) number of objectives that were stated in performance/practical terms presumed to test skills and application of knowledge. Data collected were analyzed using frequency counts, percentages, and ratios. Results revealed that a significant proportion of sampled course materials contained adequate number of learning objectives that were stated in measurable behavioural terms (knowledge level), but found deficient in performance-based objectives (practical skills). From these findings, it was concluded that NOUN should adopt practical skill-based education approach in the design and development of course materials while course modules should contain as much practical knowledge as with theoretical knowledge. Also, all course materials that are deficient in practical skill activities should be reviewed and updated in line with current realities. In the study the two terms ’practical skills learning’ and ’competency-based learning’ mean the same and were used interchangeably throughout the study.